Implementation of extracurricular activities of pencak silat pagar nusa towards students' discipline of class xi sma darut tauhid katol barat - Faizah, Faizah; Indriani, Dian Eka; Trinura N, Anindita (Universitas Tanjungpura, 2024)
The social and cultural conditions of Indonesian society are increasingly concerning lately. Various social problems have emerged, the education sector has been affected by these social problems, causing damage to moral values, so the importance of discipline values is one of the values that are developed because through these discipline values, other values will be formed. The formation of disciplined students is a formulation of the school's goals. This is because the purpose of the school Discipline is behavior that reflects orderly behavior and obeys various applicable provisions and regulations, Extracurricular Pencak Silat Pagar Nusa Against the discipline of Class 2 Students of SMA Darut Tauhid, Extracurricular Pencak Silat Pagar Nusa at SMA Darut Tauhid is an activity carried out outside the classroom and in it there is a Self-Defense activity that is carried out 2X in one week precisely on Friday afternoon after the Dhuhur prayer, and Sunday morning at 8 o'clock, Pencak Silat which is also an extracurricular at SMA Darut Tauhid Katol Barat is an activity that is a forum for developing the potential of participants and also exploring the interests and talents of students, The form of Implementation of extracurricular pencak silat activities is that students are able to follow certain rules that have been made. because with the existence of the Pencak Silat pagar nusa extracurricular, student discipline becomes better, for example students arrive on time to school, do not break school rules, wear neat clothes and always hand in their assignments on time